Residual Stresses and Nanoindentation Testing of Films and Coatings - Wang, Haidou (Springer Singapore, 2018)
This book covers the basic principles and application of nanoindentation technology to determine residual stresses in films and coatings. It briefly introduces various detection technologies for measuring residual stresses, while mainly focusing on nanoindentation. Subsequently, nanoindentation is used to determine residual stresses in different types of films and coatings, and to describe them in detail. This book is intended for specialists, engineers and graduate students in mechanical design, manufacturing, maintenance and remanufacturing, and as a guide to the practice of production with social and economic benefits.